Identifikasi Pola Redistribusi Tanah Yang Tidak dan Telah Mengalami Longsor Berdasarkan Nilai Suseptibilitas Magnetik di Daerah Batu Busuk Kota Padang - Putri, Rosyie Sahara; Budiman, Arif (Universitas Andalas, 2024)
The research has been carried out to identify patterns of soil redistribution based on magnetic susceptibility values in the Batu Busuk area, Lambung Bukit Village, Pauh District, Padang City. The sample was carried out at three locations, namely Location A (experienced landslides), Location B (not experienced landslides), and Location C (not experienced landslides), with a track length of 40 meters for each location, which has 5 points with variations in depth of 10, 20, 30, 40 and 50 cm. The magnetic susceptibility of the sample was measured using a Bartington Magnetic Susceptibility Meter with a low frequency of 0.465 kHz and a high frequency of 47 kHz. The results showed that most of the samples from Location A and Location C had Ï‡fd (%) value of less than 4.0%, while for Location B, it was the opposite. The sample Location B has a pattern where the value of Ï‡fd increases with increasing Ï‡lf value, not so for the samples for Locations A and C. The susceptibility values for the samples for Location B and Location C decrease with increasing sampling depth, while the sample for Location A fluctuates. The pattern of soil redistribution based on the distribution of sample magnetic susceptibility values for Location B and Location C is relatively more even. On the contrary, Location A. Location A and Location C have experienced erosion, where the erosion rate in Location A is higher than in Location C. In contrast, the soil conditions in Location B are relatively stable.